Sensitive electrochemical detection of arsenic (III) using gold nanoparticle modified carbon nanotubes via anodic stripping voltammetry. - Xiao, L; Wildgoose, G; Compton, R (2008)
Gold nanoparticles were deposited electrolessly on multiwalled carbon nanotubes (CNTs) via in situ reduction of HAuCl(4) by NaBH(4). The resulting gold covered nanotubes were immobilised onto the surface of a glassy carbon electrode via evaporation of a suspension in chloroform. Anodic stripping voltammetry was performed with the modified electrode in As(III) solutions. A limit of detection (LOD based on 3 sigma) of 0.1 microgL(-1) was obtained but more importantly a sensitivity of 1985 microA microM(-1) was obtained with square wave voltammetry (SWV) in an optimised system with a deposition time of 120s. These values, particularly the high sensitivity compare favourably with previously reported methods in the area of electrochemical arsenic detection.